Applying the Domain-Mapping-Matrix to Identify the Appropriate Level of Detail of Simulation Models for Virtual Commissioning. Issue 10 (2015) - Schmidt, Philipp Puntel; Fay, Alexander
Abstract: Virtual commissioning (VC) as a method can be applied in many industries. The target of VC is to test control code as early as possible and enable thereby a smoother and faster execution of real commissioning. A crucial point in conducting simulation particularly within VC is that used simulation models must be sufficiently meaningful regarding the appropriate use case. An appropriate level of detail of used simulation models is therefore essential. A systematic classification of which parts of an automated plant should be simulated at what respective level of detail is, however, not available at present time. The following article follows the hypothesis that interactions between (production) processes and resources, emerged during the engineering process, allow for the identification of influence factors that play a key role in identifying the appropriate level of detail of simulation models. The Domain-Mapping-Matrix (DMM) and a rule-based approach can be used to analyse these interactions.